Oocytes With Smooth Endoplasmic Reticulum Aggregates May Not Impact Blastocyst Euploidy Rate - Xu, Jian; Yang, Li; Chen, Zhi-Heng; Yin, Min-Na; Chen, Juan; Sun, Ling (Frontiers in Endocrinology, 2022)
Objective To investigate whether the euploidy rate of blastocysts derived from smooth endoplasmic reticulum aggregates (SERa) positive cycles and oocytes are impacted. Design Retrospective cohort study. Method(s) A total of 601 preimplantation genetic testing (PGT) cycles with at least one oocyte retrieved in our center between April 2017 and May 2021 were initially included in the study. Women>35 years and PGT cycles with chromosomal structural rearrangements (PGT-SR) were excluded. Embryological and blastocyst ploidy outcomes were compared among SERa+ oocyte, sibling SERa- oocytes and oocytes in SERa- cycles. Results No significant difference was observed among the SERa+ oocyte group, sibling SERa- oocyte group, and SERa- cycle group in the normal fertilization rate (82.1% vs. 77.8% vs. 83.1%, respectively, P=0.061), blastocyst formation rate (71.0% vs. 72.5% vs. 68.4%, respectively, P=0.393), good quality blastocyst formation rate (46.4% vs. 48.3% vs. 42.6%, respectively, P=0.198). No significant difference was observed in the euploidy rate (50.0% vs. 62.5% vs. 63.3%, respectively, P=0.324), mosaic rate (12.5% vs. 9.7% vs. 13.4%, respectively, P=0.506), and aneuploidy rate (37.5% vs. 27.8% vs. 23.2%, respectively, P=0.137) among the three groups. Conclusion Our results suggest that the euploidy rate of blastocysts derived from SERa+ cycles and oocytes may not be impacted.